The Effect of Pregelatinization with Heat and Moisture Treatment on Physicochemical and Pasting Characteristics of Red Glutinous Rice Flour - Jhauharotul Muchlisyiyah; Hera Sisca Prasmita; Teti Estiasih; Ratna Palupi Nurfatimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Red glutinous rice is native from Pacitan and is still limited to local region consumption. The color of the rice flour showed that it has bioactive content, which is the potential to wider the use. The effect of pregelatinization using heat and moisture treatment by boiling on physicochemical (starch, amylose, anthocyanin, gel consistency, Lab color, SEM figure) and pasting properties of red glutinous rice flour was determined. The time and temperature of pregelatinization were 5, 10, and 15 minutes and 50°C, 60°C, and 60°C. The experiment was done with a completely randomized design with three replications. Starch content range to 62-77%, amylose content 3.29-5.75%, anthocyanin 2.64-6.71 mg/100g, Moisture 6.16-7.45, L 72.5-73.95, redness 5.11-6.00, yellowness 8.87-9.62, and gel consistency 9.7-12 cm. the increase of time and temperature of pregelatinization lead to decrease of amylose, starch, and anthocyanin content, and viscosity. After pregelatinization, the setback viscosity was lower it means that the rate of retrogradation is lower than native starch. SEM figure also showed that pregelatinization using heat and moisture treatment did not destroy the starch granules.